2019
DOI: 10.1002/crat.201900044
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dynamic Recrystallization in the Plastic Deformation Zone of Vibration Cast‐Rolling

Abstract: In the comparative experiments of vibration and non-vibration cast-rolling, it is found that the vibration can significantly enhance the dynamic recrystallization effect in the plastic deformation stage during cast-rolling. In order to explore the strengthening mechanism, the physical simulation experiment and the numerical simulation based on Yada model are used to study the plastic deformation stage of the cast-rolling process. The research results show that the Yada model can accurately calculate the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…However, the rolling process, similar to the third method, has made significant progress in fabricating LVP strips in recent years. [45][46][47] Du et al [48][49][50] proposed a vibration TRC process, as shown in Fig. 8(a).…”
Section: Longitudinal Variable Profiled Stripmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rolling process, similar to the third method, has made significant progress in fabricating LVP strips in recent years. [45][46][47] Du et al [48][49][50] proposed a vibration TRC process, as shown in Fig. 8(a).…”
Section: Longitudinal Variable Profiled Stripmentioning
confidence: 99%
“…Vibration TRC process: (a) schematic diagram, (b) comparison of cast-rolling zone, (c) comparison of strips. [48][49][50] (Online version in color.) interfacial bonding can be formed between the substrate and cladding.…”
Section: Circular Section Productsmentioning
confidence: 99%